Clinical reasoning strategies of speech pathology students - Soriano, Jennifer U.; Erlyn A. Sana, PhD (2011)
Clinical reasoning is a basic competency of speech pathologists. Filipino speech pathology educators are faced with the challenge of developing the students' clinical reasoning. In recent years, studies of clinical reasoning in Filipino speech pathologists have gained momentum. However, there are no data on the thought processes of students. This information is crucial for illustrating the development of clinical reasoning. Understanding how interns are thinking and how they use their discipline's specific knowledge will help speech pathology educators identify critical concepts and how to teach them. It will also lead to the development of teaching innovations that will facilitate the development of sound clinical reasoning. The qualitative case study described the clinical reasoning of speech pathology interns by collecting verbal protocol and conducting a focus group discussion (FGD) with six interns of the Bachelor of Science in Speech Pathology program in the College of Allied Medical Professions in the University of the Philippines Manila for the School-Year 2010-2011. All participants underwent clinical internship prior to data collection. In pairs, the interns were asked to discuss their plans for assessing and managing the communication disorder of a client. In the FGD, they were asked to ask for their personal insights about their clinical reasoning process. Their discussions with their partner and focus group discussion were audio-recorded and transcribed verbatim. Thematic analysis was conducted so as to identify the prevailing ideas. This study identified different characteristics of speech pathology interns' clinical reasoning. Assessment and management planning involved activation of prior knowledge and various thinking process. Interns were observed to use ten thinking skills during assessment and management planning. These thinking skills, namely: seeking information, recognizing, labeling, applying tool protocol, phrasing, organizing, categorizing, comparing, analyzing causal relationship, prioritizing, and looking forward, were found to be similar to those initially presented in the revised Bloom's Taxonomy (Anderson & Krathwohl, 2001) and Core Thinking Skills (Manzano et al., 1988). Use of these ten thinking skills was linked to different clinical tasks. Furthermore, the characteristics of the clinician, client, and work setting framed clinical reasoning. The objective of planning, that is, either to determine the scope of the problem by identifying the client's current functioning and the cause of the problem or to make the assessment and management plan appropriate for the client also affected clinical reasoning. And lastly, interns showed awareness of their own thinking but evidence for controlling their own thinking was limited. Results of this data implied that the six speech pathology interns developed basic knowledge base and thinking skills needed for planning for assessment and management.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Melflor A. Atienza MD MHPEd, Reader/Critic; Maria Concepcion C. Cabatan MHPEd, Member; Jocelyn Marzan CCC-SLP, Member; Esmerita Rotor PRTP MAEd, Member.
Keywords: Clinical Competence; Decision Making